Nicotine and cannabis vaping among early high school adolescents: Disparities of use across sociodemographic characteristics and associations with psychosocial factors - Christine M. Steeger; Charleen J. Gust; Alyssa F. Harlow; Christopher Cambron; Jessica Barrington-Trimis; Katie Massey Combs; Ashley Brooks-Russell; Karl G. Hill (Addictive Behaviors Reports)
Objective. This study examines whether adolescent nicotine and cannabis vaping types (i.e., nicotine-only, cannabis-only, and dual use) differ across sociodemographic and school characteristics (e.g., age, gender, sexual identity, race/ethnicity, socioeconomic status [SES], school setting/type), and associations of vaping types with psychosocial factors. Methods. From 2021 to 2022, 9th and 10th grade adolescents (N = 2,476) in Colorado and Ohio participated in a survey measuring vaping behaviors and psychosocial factors including substance use attitudes, alcohol use, mental health, aggression, and family and school risk and protective factors. Results. Past month vaping prevalence was 89.7 % for non-use, 5.9 % for nicotine-only, 1.0 % for cannabis-only, and 3.4 % for dual use. Chi-square tests of independence showed several significant sociodemographic differences for past month vaping: higher nicotine-only vaping prevalence for females (vs. males) (p < 0.001), higher nicotine-only and dual vaping prevalence for LGB+ (vs. heterosexual) youth (ps < 0.01), higher dual vaping prevalence for Hispanic and multiethnic (vs. White) adolescents (p < 0.001), and higher nicotine-only, cannabis-only, and dual vaping prevalence for lower (vs. higher) mother education (ps < 0.001). Regression models examining associations between vaping types (vs. non-use) and psychosocial factors indicated a robust pattern of worse levels of substance use attitudes, alcohol use, mental health, aggression, and family and school factors for nicotine-only and dual users. Results followed a similar pattern but to a lesser degree for cannabis-only users. Conclusions. Findings identify characteristics of adolescents who may be particularly vulnerable to higher vaping risk (females, LGB+, Hispanic, multiethnic, low SES) and suggest needs for preventive interventions aimed to reduce all types of vaping for better adolescent behavioral health.